Götz Hillig and his search for the true Makarenko. What did he find? - Waterkamp, Dietmar (International Dialogues on Education Journal, 2018)
Beginning in the twenties of the previous century, the writings of Anton Semjonovitch Makarenko, an educator who was born in the Ukranian part of the former Russia and mainly spoke and wrote in Russian, attracted much attention among educators not only in the Russian-speaking world and in communist states but also in the Western world and other countries. He lived from 1888-1939, which means that the bulk of his writings were published in the Stalinist period of the Soviet Union. The most detailed investigations into his writings and professional and private life were accomplished by the West German researcher Götz Hillig (born 1938) at the University of Marburg. He dedicated his professional life to the famous educator and produced a critical edition of Makarenko’s important works together with a multitude of analyses and commentaries covering most of the disputed questions regarding his life and work. To most of them he found a convincing answer. So far, Hillig’s immense, yet diversely published work has not been explored to see which new picture of Makarenko can be drawn from Hillig’s scrutiny. He himself did not finish this task as he focussed on delivering a fully clarified basis of texts and a complete history of Makarenko’s life. This article underpins the necessity of drawing conclusions from Hillig’s works and gives a first idea of the change in our picture of Makarenko which flows from Hillig’s work.